Trends in Mathematical Education: Methodologies in the Teaching-Learning Process in the Integrated Technical Courses of the Federal Institutes of Brasília - Alvim, Brenner Gomes; Oliveira, Ana Maria (Cadernos de Educação Tecnologia e Sociedade, 2022)
The article presents the results of the investigation that was carried out for the Completion Work of a Degree in Mathematics at the Federal Institute of Brasília. The research was about the methodologies used in the teaching-learning of the discipline of Mathematics and the most applicable during the teaching process, in the classes of the integrated technical education of high level at the Federal Institute of Brasília. The investigation aimed to verify the methodological contributions of the Trends in Mathematics Education (TEM) that are part of the teaching and learning process in the integrated technical education of high school on the campuses of the Instituto Federal de Brasília, which obtained good results in relation to the PISA ranking. Noting the METs: Ethnomathematics, Problem Solving, Philosophy of Mathematics Education, Mathematical Modeling, History of Mathematics, Mathematical Games and Information and Communication Technologies (ICT) in Mathematics Education. The mixed method was used, comprising the quantitative methods, in the comparison of the answers of the questionnaires in relation to the closed questions, and qualitative, in the textual analysis of the answers of the open questions, analyzing them through categories. The results of the 10 professors who proposed to participate in the investigation showed that Problem Solving was the MET that predominated and contributed to the positive results, as well as the application of the diversities of MET and teacher qualification, are factors that collaborate to a positive evaluation in relation to the excellence indices of the students of the Instituto Federal de Brasília.